A large volute casting and a method for manufacturing the same
By using a ternary synergistic spheroidizing system consisting of yttrium-based heavy rare earth spheroidizing agent, MgO@CaO core-shell structure spheroidizing agent, and graphite morphology regulating elements, the problem of insufficient mechanical properties and corrosion resistance in large volute castings has been solved, achieving high strength, high toughness, and excellent corrosion resistance, making it suitable for fluid machinery equipment such as water pumps, fans, and compressors.
Patent Information
- Application Number
- CN202511377216.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-25
- Publication Date
- 2025-12-09
- Estimated Expiration
- 2045-09-25
AI Technical Summary
Existing large volute castings have shortcomings in mechanical properties and corrosion resistance, especially in high-pressure, high-impact, and complex media corrosion environments. Traditional spheroidizing processes suffer from problems such as spheroidization decay, unstable graphite sphere morphology, and uneven microstructure.
A ternary synergistic spheroidizing treatment system, consisting of yttrium-based heavy rare earth spheroidizing agent, MgO@CaO core-shell structure spheroidizing agent, and graphite morphology regulating elements, combined with a stepwise addition process, was developed. Through precise control of chemical composition and microstructure design, a composite structure of spheroidal graphite + ferrite + pearlite, and a transition layer at the graphite-matrix interface were formed, achieving the spheroidizing effect.
It significantly improves the spheroidization effect and microstructure stability of large volute components, achieving high strength, high toughness and excellent corrosion resistance, meeting the long-term service requirements of complex service environments, and is particularly suitable for thick cross-section castings with wall thickness of 20-100mm.
Smart Images

Figure CN120866717B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of coating materials, in particular to a large volute casting and a preparation method thereof. BACKGROUND
[0002] As the core component of fluid machinery equipment such as water pump, fan and compressor, large volute plays a key role in guiding and changing the flow direction. It usually faces harsh working conditions such as high pressure, strong impact and complex medium corrosion. With the trend of modern industrial equipment towards large-scale and high-efficiency, large volute not only needs to have excellent mechanical properties to withstand the increasing load demand, but also must have excellent corrosion resistance to adapt to various medium environments, while maintaining uniformity of microstructure and dimensional stability under complex wall thickness changes and large size conditions. Excellent mechanical properties ensure the safe and reliable operation of equipment under high-strength working conditions, while good corrosion resistance is directly related to the service life and maintenance cost of the equipment. With the continuous improvement of equipment performance requirements in the fields of marine engineering, chemical industry and energy, developing large volute materials with high strength, high toughness and excellent corrosion resistance and their preparation technology can promote the progress of fluid machinery equipment technology.
[0003] Currently, the preparation of large volute is mainly carried out by traditional nodular cast iron casting process, but there are still many technical bottlenecks and deficiencies in meeting the requirements of high performance. The traditional spheroidizing process generally faces the problems of serious spheroidizing recession and unstable graphite sphere morphology in large thick-walled castings, which is mainly due to the rapid consumption of active components of spheroidizing agent and element segregation during thick section solidification, resulting in uneven mechanical properties and low overall level of the final casting. At the same time, the conventional spheroidizing agent system is prone to over-spheroidizing under high temperature for a long time, forming harmful organizations such as flake graphite, which seriously affects the mechanical properties and corrosion resistance of the material. For example, CN120138494A discloses a low-temperature nodular cast iron, a preparation method and a QT400-18L volute casting, which uses special inoculants containing silicon, calcium and lanthanum for treatment, but has the disadvantages of unstable spheroidizing effect and limited wall thickness range. In addition, the large volute prepared by traditional process is prone to local corrosion and stress concentration under complex service environment, which is closely related to the insufficient bonding force between graphite sphere and matrix, and the insufficient density of microstructure, etc., which limits its wide application in high-end equipment field. SUMMARY
[0004] (1) The technical problem solved by the present application is to provide a large volute casting and a preparation method thereof, which solves the problems of insufficient mechanical properties and corrosion resistance of the current large volute casting.
[0005] (2) Technical solution: In order to achieve the above purpose, the present application provides the following technical solution: a preparation method of a large volute casting, comprising the following steps: S1. Preparation of iron liquid: waste steel, pig iron is smelted according to the proportion, and the composition is adjusted to C content of 3.6%-3.8%, Si content of 1.8%-2.5%, and Mn content of 0.3%-0.8%.
[0006] S2. Spheroidizing treatment: adding yttrium-based heavy rare earth spheroidizing agent, MgO@CaO core-shell structure spheroidizing agent and graphite morphology regulating element to the iron liquid, the addition amount of yttrium-based heavy rare earth spheroidizing agent is 0.8%-1.5% of the weight of the iron liquid, the addition amount of MgO@CaO core-shell structure spheroidizing agent is 0.3%-0.8% of the weight of the iron liquid, the addition amount of graphite morphology regulating element is 0.005%-0.05% of the weight of the iron liquid, the treatment temperature is 1460-1480℃, and the spheroidizing treatment time is 3-8 minutes.
[0007] S3. Inoculation treatment: adding ferrosilicon-based stream inoculant at a temperature of 1420-1450℃, the addition amount of inoculant is 0.06%-0.07% of the weight of the iron liquid, and the inoculation time is 1-3 minutes.
[0008] S4. Pouring forming: pouring the treated iron liquid into the volute casting mold, and controlling the pouring temperature to be 1380-1420℃.
[0009] The MgO@CaO core-shell structure spheroidizing agent comprises an MgO core and a CaO outer shell layer coated on the outer surface of the MgO core.
[0010] The graphite morphology regulating element is selected from one or more of bismuth, antimony and tellurium.
[0011] The invention adopts a ternary synergistic spheroidizing treatment system design of yttrium-based heavy rare earth spheroidizing agent, MgO@CaO core-shell structure spheroidizing agent and graphite morphology regulating element, which is mainly used for enhancing the mechanical properties and corrosion resistance of large volute castings. The yttrium-based heavy rare earth spheroidizing agent plays a leading role in the spheroidizing process, and provides a stable environment for the nucleation of graphite spheres through the strong deoxidization and desulfurization ability of rare earth elements. The addition of yttrium element effectively improves the high-temperature stability of the spheroidizing agent, and establishes a reliable foundation for the subsequent spheroidizing process. The unique design of the MgO@CaO core-shell structure spheroidizing agent is that the core-shell structure can realize step-by-step release of spheroidizing elements. The MgO core provides continuous spheroidizing effect, and the CaO shell layer further optimizes the morphology and distribution of graphite spheres through Ca-Mg synergistic effect. This layered release mechanism effectively prolongs the effective spheroidizing time, especially suitable for the long-time solidification process of large thick-walled castings. The introduction of graphite morphology regulating elements bismuth, antimony and tellurium fine-tunes the graphite morphology from another dimension. These elements can effectively inhibit the formation of chunky graphite and promote the regular growth of spherical graphite. The synergistic mechanism of the three spheroidizing treatment components is that the yttrium-based spheroidizing agent provides a stable spheroidizing core, the MgO@CaO core-shell structure spheroidizing agent realizes time extension and space optimization of the spheroidizing process through core-shell separation release, and the graphite morphology regulating elements accurately control the graphite growth orientation. The three components cooperate with each other to form a multi-level and multi-dimensional spheroidizing regulation system, which not only significantly improves the spheroidizing rate of graphite, but also optimizes the size distribution and morphology quality of graphite spheres, and finally realizes the uniformity of the organizational structure and the overall performance improvement of large volute castings.
[0012] Further, the yttrium-based heavy rare earth spheroidizing agent contains Y 5%-15%, Mg 3%-8%, Si 40%-50%, Ca 1%-3%, Al 0.5%-2%, and the balance is Fe.
[0013] Further, the particle size of the MgO core in the MgO@CaO core-shell structure spheroidizing agent is 50-150 μm, the thickness of the CaO shell layer is 25-45 μm, the porosity of the MgO core is 8-15%, and the porosity of the CaO shell layer is 12-20%.
[0014] Further, the spheroidizing treatment adopts a step-by-step addition method, the yttrium-based heavy rare earth spheroidizing agent is added first for preliminary spheroidizing, and after 30-60 seconds, the MgO@CaO core-shell structure spheroidizing agent and the graphite morphology regulating element are added at the same time for secondary spheroidizing optimization. The temperature difference of the two-step spheroidizing is controlled within the range of 20-40℃.
[0015] Further, the yttrium-based spheroidizing agent provides a stable spheroidizing core, and the MgO@CaO spheroidizing agent optimizes the graphite spheroidization morphology through the Ca-Mg synergistic effect, and the graphite morphology control element inhibits the formation of chunky graphite, and the three synergies realize the extension of the spheroidization effective time to 180-240 seconds.
[0016] Further, the preparation method of the MgO@CaO core-shell structure spheroidizing agent comprises the following steps: A1. Core solution preparation: one or more soluble magnesium salts of magnesium sulfate, magnesium chloride or nitric acid magnesium are dissolved in deionized water to prepare a magnesium ion solution with a concentration of 0.8-2.5 mol / L, sodium dodecyl sulfate is added as a dispersing agent, the addition amount is 0.1%-0.5% of the weight of the magnesium salt, ammonia water is added as a pH adjuster, the pH value is controlled to be 9.0-11.0, and the stirring time is 15-30 minutes.
[0017] A2. Precipitation reaction: ammonia water solution with a concentration of 2-5 mol / L is added dropwise into the magnesium ion solution at a rate of 1-3 mL / min to make the magnesium ion completely precipitate, and the magnesium hydroxide precipitate is generated after reacting at 60-90℃ for 1-3 hours.
[0018] A3. Nucleation by calcination: after the magnesium hydroxide precipitate is filtered, washed and dried, it is calcined at 800-1000℃ for 2-4 hours to obtain the MgO core.
[0019] A4. Shell coating: the MgO core is dispersed in a calcium chloride solution with a concentration of 1.0-3.0 mol / L, stirred for 10-20 minutes, and then a sodium carbonate solution with a concentration of 0.5-2.0 mol / L is added for co-precipitation reaction, and the calcium carbonate shell is generated in situ on the surface of the MgO core after reacting for 2-4 hours.
[0020] A5. Thermal decomposition conversion: the composite particles coated with calcium carbonate are thermally decomposed at 900-1100℃ for 2-3 hours, and the calcium carbonate is decomposed into CaO to form a CaO shell layer.
[0021] A6. Surface modification: under an inert atmosphere, cool at a rate of 5-10℃ / min, and introduce water vapor with a volume flow rate of 50-200 mL / min for surface modification during the cooling process, and the modification time is 30-60 minutes, which enhances the core-shell interface bonding force, and the MgO@CaO core-shell structure spheroidizing agent is obtained.
[0022] The application adopts precisely controlled component proportioning of yttrium-based heavy rare earth nodulizer, MgO@CaO core-shell structure nodulizer with specific particle size and porosity, and step-by-step nodulizing process design, and is mainly used for enhancing nodulizing effect and structure stability of large volute castings. The precise proportioning design of Y, Mg, Si, Ca and Al components in the yttrium-based heavy rare earth nodulizer aims to build a multi-element synergistic nodulizing system, in which yttrium element serves as a strong deoxidizing and desulfurizing agent to create a clean metallurgical environment for nodulizing reaction, magnesium element provides main nodulizing effect, silicon element adjusts the melting point and fluidity of the nodulizer, calcium element enhances the persistence of the nodulizing effect, and aluminum element further purifies the molten iron. These elements form a composite nodulizing core under high temperature conditions, laying a foundation for the regular growth of graphite nodules. The microstructure design of the MgO@CaO core-shell structure nodulizer embodies the concept of hierarchical regulation. The specific particle size MgO core and the CaO outer shell layer with precise thickness obtained by liquid phase method are combined with respective porosity control to realize the gradient release mechanism of nodulizing elements. The MgO core slowly dissolves at high temperature to provide a sustained magnesium source, and the CaO outer shell layer releases calcium ions at the right time to produce a synergistic effect with magnesium ions. This core-shell separation design enables precise regulation of the nodulizing reaction in time and space. The design of the step-by-step addition process further strengthens the synergistic effect of multiple components. The yttrium-based heavy rare earth nodulizer is first added to perform preliminary nodulizing to establish a stable reaction basis, and then the MgO@CaO core-shell structure nodulizer and graphite morphology regulating elements are simultaneously added under the condition of slightly reduced temperature for secondary optimization. This time sequence control ensures that each component can play its respective role under the most suitable temperature conditions, avoiding reaction competition and effect offset caused by simultaneous addition, and finally realizing a triple synergistic mechanism of the yttrium-based nodulizer providing a stable nodulizing core, the MgO@CaO nodulizer optimizing graphite nodule morphology through Ca-Mg synergistic effect, and the graphite morphology regulating elements inhibiting the formation of flaky graphite, so that the nodulizing effective time is significantly prolonged, providing a sufficient process window for uniform structure formation of large thick-walled volute castings.
[0023] The application also discloses a large volute casting prepared by the above method; and the chemical composition of the large volute casting is as follows in terms of percentage by weight: C 3.6%-3.8%, Si 1.8%-2.5%, Mn 0.3%-0.8%, P ≤0.05%, S ≤0.02%, Cu 0.3%-0.8%, Sn ≤0.05%, Y 0.005%-0.03%, graphite morphology regulating element 0.005%-0.05%, residual rare earth ≤0.03%, and the balance being Fe and inevitable impurities.
[0024] Further, the microstructure of the large volute casting comprises spheroidal graphite + ferrite + pearlite, the graphite nodulizing rate is ≥95%, the average diameter of the graphite nodules is 15-30 μm, and there is no flaky graphite.
[0025] Further, the graphite ball and the base interface exist a composite transition layer rich in Ca, Mg, C, O, Y elements, the average thickness is 12-18.5 mu m, effectively prevents the formation of broken block graphite and improves the interface bonding strength.
[0026] Further, the application of the large volute casting in water pump, fan or compressor, the tensile strength of the large volute casting is greater than or equal to 500 MPa, the elongation is greater than or equal to 7%, the Brinell hardness is 170-220 HB, has excellent corrosion resistance and mechanical properties, and is suitable for thick section castings with a wall thickness of 20-100 mm.
[0027] The present application adopts precise chemical composition control, spherical graphite + ferrite + pearlite composite structure design and interface transition layer construction design, and is mainly used for enhancing the comprehensive mechanical properties and corrosion resistance of the large volute casting. The precise design of the chemical composition reflects the concept of multi-element synergistic regulation, the precise control of the carbon content provides sufficient carbon source for the analysis of the graphite ball, the optimization of the silicon content promotes the graphitization process and strengthens the matrix structure, the appropriate addition of the manganese element effectively refines the pearlite structure and improves the strength and toughness of the material, the strict limitation of the phosphorus and sulfur content ensures the purity of the matrix and the interface bonding quality, the addition of the copper element further enhances the corrosion resistance of the material, and the residual of the yttrium element and the graphite shape regulating element continues to play the role of structure optimization. These elements interact during solidification to form a stable and efficient alloying system. The design of the microstructure highlights the mechanism of multi-phase synergistic strengthening, the spherical graphite as the basic phase provides good plasticity and toughness, the ferrite matrix ensures the processability and ductility of the material, and the pearlite structure significantly improves the strength level. The coordinated cooperation of the three-phase structure realizes the organic unity of strength and toughness, and the high spheroidization rate and appropriate graphite ball size distribution ensure the stress dispersion effect and crack propagation resistance. The construction of the interface transition layer is the key innovation point of the present application, the composite transition layer rich in Ca, Mg, C, O, Y elements forms a functional gradient region between the graphite ball and the matrix. This transition layer not only effectively eliminates the weak link between the graphite ball and the matrix in the traditional nodular iron, but also significantly improves the interface bonding strength through the synergistic effect of multiple elements. The presence of Ca and Mg elements improves the wettability and bonding state of the interface, and the Y element further purifies the interface area and inhibits the formation of harmful phases, thereby realizing smooth transition from the graphite ball to the matrix. This interface design enables the material to effectively transfer stress and prevent crack initiation and propagation at the interface when subjected to external load, ultimately achieving overall improvement of tensile strength, elongation and Brinell hardness, and obtaining excellent corrosion resistance, especially suitable for the harsh service requirements of thick section volute castings in water pumps, fans, compressors and other equipment.
[0028] (3)Beneficial technical effects: The present application adopts a ternary synergistic spheroidizing treatment system of yttrium-based heavy rare earth spheroidizing agent, MgO@CaO core-shell structure spheroidizing agent and graphite morphology regulating element, combined with step-by-step adding process and accurate composition control, to obtain the following significant beneficial effects: 1. The spheroidizing effect is significantly improved: the ternary synergistic spheroidizing system realizes the extension of the spheroidizing effective time to 180-240 seconds, the graphite spheroidizing rate reaches ≥95%, the average diameter of graphite spheres is controlled within 15-30 μm, and the formation of fragmented graphite is completely eliminated, which is significantly superior to the effect stability and durability of the traditional spheroidizing process.
[0029] 2. Microstructure optimization: The ideal composite structure of spheroidal graphite + ferrite + pearlite is obtained, the interface between graphite spheres and the matrix forms a composite transition layer rich in Ca, Mg, C, O and Y elements, with an average thickness of 12-18.5 μm, effectively improving the interface bonding strength and eliminating the weak link of the traditional spheroidal graphite interface.
[0030] 3. Comprehensive improvement of mechanical properties: The tensile strength of large volute castings reaches ≥500 MPa, the elongation is ≥7%, and the Brinell hardness is controlled within 170-220 HB, achieving a good balance of strength, toughness and hardness, and the mechanical properties are significantly improved compared with the traditional process.
[0031] 4. Excellent corrosion resistance: Through accurate chemical composition control and microstructure optimization, especially reasonable addition of copper element and strict limitation of harmful elements, the castings have excellent corrosion resistance, which meets the long-term service requirements in complex medium environment.
[0032] 5. Strong process adaptability: This method is especially suitable for thick section castings with a wall thickness of 20-100 mm, solving the technical problems of spheroidization recession and uneven structure in the long-time solidification process of large volute castings, and the process stability and reproducibility are good.
[0033] 6. Wide application range: The prepared large volute castings are suitable for key fluid mechanical equipment such as water pumps, fans and compressors, which can meet the use requirements of high pressure, strong impact and complex medium corrosion in severe working conditions, and have important engineering application value. BRIEF DESCRIPTION OF DRAWINGS
[0034] Figure 1 The morphology diagram of the MgO@CaO core-shell structure spheroidizing agent prepared in Example 2 of the present application.
[0035] Figure 2 The XRD phase analysis diagram of the MgO@CaO core-shell structure spheroidizing agent prepared in Example 2 of the present application.
[0036] Figure 3Elemental mapping of graphite nodule and its outer transition layer in the casting prepared for Example 2 of the present application.
[0037] Figure 4 Morphology of graphite nodule and its outer transition layer in the casting prepared for Comparative Example 1 of the present application.
[0038] Figure 5 Comparison chart of strength performance of the castings prepared for the Examples and Comparative Examples of the present application.
[0039] Figure 6 Comparison chart of toughness performance of the castings prepared for the Examples and Comparative Examples of the present application.
[0040] Figure 7 Comparison chart of hardness and fatigue performance of the castings prepared for the Examples and Comparative Examples of the present application. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below with reference to the drawings in the embodiments of the present application.
[0042] Example 1: A preparation method of a large volute part, comprising the following steps: S1. Preparation of iron liquid: scrap steel, pig iron are smelted according to the proportion, and the composition is adjusted to C content of 3.7%, Si content of 2.1%, and Mn content of 0.5%.
[0043] S2. Spheroidizing treatment: yttrium-based heavy rare earth spheroidizing agent, MgO@CaO core-shell structure spheroidizing agent and graphite morphology regulating element are added to the iron liquid, the addition amount of yttrium-based heavy rare earth spheroidizing agent is 1.1% of the weight of the iron liquid, the addition amount of MgO@CaO core-shell structure spheroidizing agent is 0.5% of the weight of the iron liquid, and the addition amount of graphite morphology regulating element is 0.02% of the weight of the iron liquid, the treatment temperature is 1470℃, and the spheroidizing treatment time is 5 minutes.
[0044] S3. Inoculation treatment: silicon-iron-based stream inoculant is added at a temperature of 1435℃, the addition amount of inoculant is 0.065% of the weight of the iron liquid, and the inoculation time is 2 minutes.
[0045] S4. Pouring forming: the treated iron liquid is poured into a volute part casting mold, and the pouring temperature is controlled to be 1400℃.
[0046] The MgO@CaO core-shell structure spheroidizing agent of the present embodiment comprises a MgO core and a CaO outer shell layer covering the outer surface thereof; the graphite morphology regulating element is selected from one or more of bismuth, antimony and tellurium. The yttrium-based heavy rare earth spheroidizing agent comprises Y 10%, Mg 5%, Si 45%, Ca 2%, Al 1.2%, and the balance is Fe.
[0047] The particle size of the MgO core in the MgO@CaO core-shell structure spheroidizing agent of the embodiment is 100 pm, the thickness of the CaO shell layer is 35 pm, the porosity of the MgO core is 11%, and the porosity of the CaO shell layer is 16%.
[0048] The spheroidizing treatment of the embodiment adopts a step-by-step addition mode, and yttrium-based heavy rare earth spheroidizing agent is first added for preliminary spheroidizing, and then MgO@CaO core-shell structure spheroidizing agent and graphite morphology regulating elements are simultaneously added after 45 seconds of reaction for secondary spheroidizing optimization, and the temperature difference of the two-step spheroidizing is controlled within 30°C.
[0049] The yttrium-based spheroidizing agent of the embodiment provides a stable spheroidizing core, the MgO@CaO spheroidizing agent optimizes the graphite sphere morphology through the Ca-Mg synergistic effect, and the graphite morphology regulating elements inhibit the formation of flaky graphite.
[0050] The preparation method of the MgO@CaO core-shell structure spheroidizing agent of the embodiment includes the following steps: A1. Core solution preparation: one or more soluble magnesium salts of magnesium sulfate, magnesium chloride or magnesium nitrate are dissolved in deionized water to prepare a magnesium ion solution with a concentration of 1.6 mol / L, sodium dodecyl sulfate is added as a dispersing agent, the addition amount is 0.3% of the weight of the magnesium salt, ammonia water is added as a pH adjuster, the pH value is controlled at 10.0, and the stirring time is 22 minutes.
[0051] A2. Precipitation reaction: ammonia water solution with a concentration of 3.5 mol / L is added dropwise into the magnesium ion solution at a rate of 2 mL / min to completely precipitate the magnesium ions, and the magnesium hydroxide precipitate is generated after reacting at 75°C for 2 hours.
[0052] A3. Calcination nucleation: after the magnesium hydroxide precipitate is filtered, washed and dried, it is calcined at 900°C for 3 hours to obtain the MgO core.
[0053] A4. Shell coating: the MgO core is dispersed in a calcium chloride solution with a concentration of 2.0 mol / L, and after stirring for 15 minutes, a sodium carbonate solution with a concentration of 1.2 mol / L is added for co-precipitation reaction, and the calcium carbonate shell is generated in situ on the surface of the MgO core after reacting for 3 hours.
[0054] A5. Thermal decomposition conversion: the composite particles coated with calcium carbonate are thermally decomposed at 1000°C for 2.5 hours, and the calcium carbonate is decomposed into CaO to form the CaO shell layer.
[0055] A6. Surface modification: cooling at a rate of 7°C / min under an inert atmosphere, and surface modification is performed by introducing water vapor with a volume flow rate of 120 mL / min during the cooling process, and the modification time is 45 minutes, which enhances the interfacial bonding force of the core-shell structure, and the MgO@CaO core-shell structure spheroidizing agent is obtained.
[0056] A large volute part of the embodiment is prepared by the above method.
[0057] The chemical composition of the large volute part of the embodiment is as follows in terms of percentage by weight: C 3.7%, Si 2.1%, Mn 0.5%, P ≤0.05%, S ≤0.02%, Cu 0.5%, Sn ≤0.05%, Y 0.018%, graphite morphology regulating element 0.025%, residual rare earth ≤0.03%, and the balance being Fe and unavoidable impurities.
[0058] The microstructure of the large volute part of the embodiment includes spheroidal graphite + ferrite + pearlite, the spheroidization rate of the graphite is ≥95%, the average diameter of the graphite spheres is 22 μm, and there is no flaky graphite.
[0059] There is a composite transition layer rich in Ca, Mg, C, O and Y elements at the interface between the graphite spheres and the matrix of the embodiment, the average thickness of the transition layer is 15.2 μm, which effectively prevents the formation of flaky graphite and improves the interface bonding strength.
[0060] Example 1 adopts a medium parameter configuration, embodying the design concept of process stability and reliability. The embodiment selects a moderate carbon content of 3.7% and a silicon content of 2.1%, cooperates with a medium strength spheroidizing treatment parameter, the yttrium-based heavy rare earth spheroidizing agent is added in an amount of 1.1%, the MgO@CaO core-shell structure spheroidizing agent is added in an amount of 0.5%, and the treatment temperature is 1470℃, forming a balanced alloying system. The average diameter of the graphite spheres in the microstructure is 22 μm, the thickness of the interface transition layer is 15.2 μm, and a good balance between strength and toughness is achieved. The process window of the embodiment is relatively wide, the operation fault tolerance is good, and it is suitable for large-scale industrial production. The application scenarios mainly include centrifugal pump volutes, general fan housings, air conditioner compressor volutes and other conventional fluid mechanical equipment under medium pressure working conditions, and it is especially suitable for manufacturing standardized products with stable performance requirements and large production batches.
[0061] Example 2: A method for preparing a large volute part, comprising the following steps: S1. Preparing an iron liquid: smelting scrap steel and pig iron in a proportion, and adjusting the components to a C content of 3.6%, a Si content of 1.8%, and a Mn content of 0.3%.
[0062] S2. Spheroidizing treatment: adding a yttrium-based heavy rare earth spheroidizing agent, a MgO@CaO core-shell structure spheroidizing agent and a graphite morphology regulating element into the iron liquid, the yttrium-based heavy rare earth spheroidizing agent is added in an amount of 0.8% of the weight of the iron liquid, the MgO@CaO core-shell structure spheroidizing agent is added in an amount of 0.3% of the weight of the iron liquid, the graphite morphology regulating element is added in an amount of 0.005% of the weight of the iron liquid, the treatment temperature is 1460℃, and the spheroidizing treatment time is 3 minutes.
[0063] S3. Inoculation treatment: add ferrosilicon-based inoculant at a temperature of 1420℃, the inoculant addition amount is 0.06% of the weight of the iron liquid, and the inoculation time is 1 minute.
[0064] S4. Pouring: pour the treated iron liquid into the spiral case part mold, and control the pouring temperature to be 1380℃.
[0065] The MgO@CaO core-shell structure inoculant of the embodiment includes an MgO core and a CaO shell layer covering the outer surface of the MgO core; the graphite morphology regulating element is selected from one or more of bismuth, antimony and tellurium. The yttrium-based heavy rare earth inoculant contains Y 5%, Mg 3%, Si 40%, Ca 1%, Al 0.5%, and the balance of Fe.
[0066] The particle size of the MgO core in the MgO@CaO core-shell structure inoculant of the embodiment is 50μm, the thickness of the CaO shell layer is 25μm, the porosity of the MgO core is 8%, and the porosity of the CaO shell layer is 12%.
[0067] The inoculation treatment of the embodiment adopts a step-by-step addition mode, first adds the yttrium-based heavy rare earth inoculant for preliminary inoculation, then simultaneously adds the MgO@CaO core-shell structure inoculant and the graphite morphology regulating element for secondary inoculation optimization after 30 seconds of reaction, and the temperature difference of the two-step inoculation is controlled within a range of 20℃.
[0068] The yttrium-based inoculant of the embodiment provides a stable inoculation core, the MgO@CaO inoculant optimizes the graphite spherical morphology through Ca-Mg synergistic effect, and the graphite morphology regulating element inhibits the formation of flaky graphite.
[0069] The preparation method of the MgO@CaO core-shell structure inoculant of the embodiment includes the following steps: A1. Core solution preparation: one or more soluble magnesium salts of magnesium sulfate, magnesium chloride or magnesium nitrate are dissolved in deionized water to prepare a magnesium ion solution with a concentration of 0.8mol / L, sodium dodecyl sulfate is added as a dispersing agent, the addition amount is 0.1% of the weight of the magnesium salt, ammonia water is added as a pH adjuster, the pH value is controlled to be 9.0, and the stirring time is 15 minutes.
[0070] A2. Precipitation reaction: ammonia water solution with a concentration of 2mol / L is added dropwise into the magnesium ion solution at a rate of 1mL / min to completely precipitate the magnesium ions, and magnesium hydroxide precipitate is generated after reaction at 60℃ for 1 hour.
[0071] A3. Nucleation by calcination: after filtration, washing and drying of the magnesium hydroxide precipitate, calcination is performed at 800℃ for 2 hours to obtain the MgO core.
[0072] A4. Coating of the shell: The MgO core is dispersed in a calcium chloride solution with a concentration of 1.0 mol / L, and after stirring for 10 minutes, a sodium carbonate solution with a concentration of 0.5 mol / L is added to perform a co-precipitation reaction, and the reaction time is 2 hours, so as to generate a calcium carbonate shell on the surface of the MgO core in situ.
[0073] A5. Thermal decomposition conversion: The composite particles coated with calcium carbonate are subjected to thermal decomposition at 900°C for 2 hours, and the calcium carbonate is decomposed into CaO to form a CaO shell layer.
[0074] A6. Surface modification: The surface is modified under an inert atmosphere at a cooling rate of 5°C / min, during which water vapor with a volume flow rate of 50 mL / min is introduced, and the modification time is 30 minutes, so as to enhance the interfacial bonding force of the core-shell structure, and obtain the MgO@CaO core-shell structure spherification agent.
[0075] A large volute part is prepared by the above method; the chemical composition of the large volute part of the present embodiment is as follows in terms of weight percentage: C 3.6%, Si 1.8%, Mn 0.3%, P ≤0.05%, S ≤0.02%, Cu 0.3%, Sn ≤0.05%, Y 0.005%, graphite morphology regulating element 0.005%, residual rare earth ≤0.03%, and the balance being Fe and unavoidable impurities.
[0076] The microstructure of the large volute part of the present embodiment includes spheroidal graphite + ferrite + pearlite, the spheroidization rate of graphite is ≥95%, and the average diameter of the graphite spheres is 15 μm, and there is no flaky graphite.
[0077] There is a composite transition layer rich in Ca, Mg, C, O and Y elements at the interface between the graphite spheres and the matrix of the present embodiment, and the average thickness is 12 μm, which effectively prevents the formation of flaky graphite and improves the interfacial bonding strength.
[0078] Example 2 adopts conservative parameter design, and pursues high stability and cost-effectiveness of the process. In this embodiment, a lower carbon content of 3.6% and a silicon content of 1.8% are selected, the spherification agent dosage is relatively small, the yttrium-based heavy rare earth spherification agent is 0.8%, the treatment temperature is 1460°C, and the reaction time is relatively short, forming fine graphite sphere structures (average diameter 15 μm) and thin interface transition layers (12 μm). This configuration reduces the cost of raw materials and simplifies process control, but still meets the basic performance requirements. The application scenarios mainly target cost-sensitive and relatively low-performance application fields, such as small water pump volutes, household fan housings, ventilation equipment under low pressure working conditions, and agricultural irrigation pump housings, and are particularly suitable for large quantities and standardized market demand.
[0079] Embodiment 3: A method for preparing a large volute part, comprising the following steps: S1. preparing an iron melt: scrap steel, pig iron are smelted in proportion, and the composition is adjusted to a C content of 3.8%, a Si content of 2.5%, and a Mn content of 0.8%.
[0080] S2. Spheroidizing treatment: yttrium-based heavy rare earth spheroidizing agent, MgO@CaO core-shell structure spheroidizing agent and graphite morphology regulating element are added to the iron melt, the yttrium-based heavy rare earth spheroidizing agent is added in an amount of 1.5% of the weight of the iron melt, the MgO@CaO core-shell structure spheroidizing agent is added in an amount of 0.8% of the weight of the iron melt, the graphite morphology regulating element is added in an amount of 0.05% of the weight of the iron melt, the treatment temperature is 1480℃, and the spheroidizing treatment time is 8 minutes.
[0081] S3. Inoculation treatment: silicon-iron-based stream inoculant is added at a temperature of 1450℃, the inoculant is added in an amount of 0.07% of the weight of the iron melt, and the inoculation time is 3 minutes.
[0082] S4. Pouring forming: the treated iron melt is poured into a volute part mold, and the pouring temperature is controlled to be 1420℃.
[0083] The MgO@CaO core-shell structure spheroidizing agent of the embodiment includes a MgO core and a CaO outer shell layer covering the outer surface of the MgO core; the graphite morphology regulating element is selected from one or more of bismuth, antimony and tellurium. The yttrium-based heavy rare earth spheroidizing agent contains Y 15%, Mg 8%, Si 50%, Ca 3%, Al 2%, and the balance is Fe.
[0084] The particle size of the MgO core in the MgO@CaO core-shell structure spheroidizing agent of the embodiment is 150μm, the thickness of the CaO outer shell layer is 45μm, the porosity of the MgO core is 15%, and the porosity of the CaO outer shell layer is 20%.
[0085] The spheroidizing treatment of the embodiment adopts a step-by-step addition method, the yttrium-based heavy rare earth spheroidizing agent is first added for preliminary spheroidizing, and after reacting for 60 seconds, the MgO@CaO core-shell structure spheroidizing agent and the graphite morphology regulating element are simultaneously added for secondary spheroidizing optimization, and the temperature difference of the two-step spheroidizing is controlled within 40℃.
[0086] The yttrium-based spheroidizing agent of the embodiment provides a stable spheroidizing core, the MgO@CaO spheroidizing agent optimizes the graphite spheroidizing through Ca-Mg synergistic effect, and the graphite morphology regulating element inhibits the formation of chunky graphite.
[0087] The preparation method of the MgO@CaO core-shell structure spheroidizing agent of the embodiment comprises the following steps: A1. Core solution preparation: one or more soluble magnesium salts of magnesium sulfate, magnesium chloride or magnesium nitrate are dissolved in deionized water to prepare a magnesium ion solution with a concentration of 2.5 mol / L, sodium dodecyl sulfate is added as a dispersing agent, the addition amount is 0.5% of the weight of the magnesium salt, ammonia water is added as a pH adjuster, the pH value is controlled to be 11.0, and the stirring time is 30 minutes.
[0088] A2. Precipitation reaction: ammonia water solution with a concentration of 5 mol / L is added dropwise into the magnesium ion solution at a rate of 3 mL / min to completely precipitate the magnesium ions, and magnesium hydroxide precipitate is generated by reacting at 90℃ for 3 hours.
[0089] A3. Nucleation by calcination: after the magnesium hydroxide precipitate is filtered, washed and dried, it is calcined at 1000℃ for 4 hours to obtain MgO core.
[0090] A4. Shell coating: the MgO core is dispersed in a calcium chloride solution with a concentration of 3.0 mol / L, sodium carbonate solution with a concentration of 2.0 mol / L is added after stirring for 20 minutes to perform a co-precipitation reaction, and a calcium carbonate shell is generated in situ on the surface of the MgO core with a reaction time of 4 hours.
[0091] A5. Thermal decomposition conversion: the composite particles coated with calcium carbonate are thermally decomposed at 1100℃ for 3 hours, the calcium carbonate is decomposed into CaO, and a CaO shell layer is formed.
[0092] A6. Surface modification: cooling is performed at a rate of 10℃ / min under an inert atmosphere, water vapor with a volume flow rate of 200 mL / min is introduced during the cooling, the modification time is 60 minutes, the core-shell interface bonding force is enhanced, and the MgO@CaO core-shell structure spheroidizing agent is obtained.
[0093] A large volute part of the embodiment is prepared by the above method; the chemical composition of the large volute part of the embodiment is as follows in terms of weight percentage: C 3.8%, Si 2.5%, Mn 0.8%, P ≤0.05%, S ≤0.02%, Cu 0.8%, Sn ≤0.05%, Y 0.03%, graphite morphology regulating element 0.05%, residual rare earth ≤0.03%, and the balance is Fe and unavoidable impurities.
[0094] The microstructure of the large volute part of the embodiment comprises spheroidal graphite + ferrite + pearlite, the graphite spheroidization rate is ≥95%, the average diameter of the graphite balls is 30 μm, and there is no flaky graphite.
[0095] The graphite ball of the embodiment has a composite transition layer rich in Ca, Mg, C, O and Y elements at the interface with the matrix, with an average thickness of 18.5 μm, effectively preventing the formation of chunky graphite and improving the interface bonding strength.
[0096] Example 3 adopts a high-performance-oriented parameter configuration to pursue maximum comprehensive performance. The highest carbon content of 3.8% and silicon content of 2.5% are selected, the dosage of spherification agent reaches the upper limit, the yttrium-based heavy rare earth spherification agent is 1.5%, the MgO@CaO core-shell structure spherification agent is 0.8%, the processing temperature is 1480℃, larger graphite balls (average diameter 30 μm) and the thickest interface transition layer (18.5 μm) are formed, and the optimal strength-toughness combination and corrosion resistance are achieved. The process parameters of this embodiment are harsh, and the requirements for equipment and operation are high, but excellent comprehensive performance can be obtained. The application scenarios mainly face high-end heavy load working conditions, such as large-scale seawater desalination pump volutes, high-pressure pump shells of chemical plants, cooling pump volutes of nuclear power plants, and large wind turbine speed increaser housings, etc. The key equipment has extremely high requirements for reliability and durability.
[0097] Example 4: A method for preparing a large volute, comprising the following steps: S1. Preparing the iron liquid: smelting scrap steel and pig iron according to the proportion, adjusting the composition to C content of 3.65%, Si content of 2.3%, and Mn content of 0.6%.
[0098] S2. Spheroidization treatment: adding yttrium-based heavy rare earth spherification agent, MgO@CaO core-shell structure spherification agent and graphite morphology control element to the iron liquid, the addition amount of yttrium-based heavy rare earth spherification agent is 1.3% of the weight of the iron liquid, the addition amount of MgO@CaO core-shell structure spherification agent is 0.6% of the weight of the iron liquid, the addition amount of graphite morphology control element is 0.03% of the weight of the iron liquid, the processing temperature is 1475℃, and the spheroidization treatment time is 6 minutes.
[0099] S3. Inoculation treatment: adding ferrosilicon-based stream inoculant at a temperature of 1440℃, the addition amount of inoculant is 0.065% of the weight of the iron liquid, and the inoculation time is 2.5 minutes.
[0100] S4. Pouring and forming: pouring the treated iron liquid into the volute casting mold, and controlling the pouring temperature to be 1395℃.
[0101] The MgO@CaO core-shell structure spherification agent of the embodiment includes a MgO core and a CaO shell layer covering the outer surface thereof; the graphite morphology control element is selected from one or more of bismuth, antimony and tellurium. The yttrium-based heavy rare earth spherification agent contains Y 12%, Mg 6%, Si 47%, Ca 2.5%, Al 1.5%, and the balance is Fe.
[0102] The particle size of the MgO core in the MgO@CaO core-shell structure spheroidizing agent of the embodiment is 120 pm, the thickness of the CaO shell layer is 38 pm, the porosity of the MgO core is 12%, and the porosity of the CaO shell layer is 17%.
[0103] The spheroidizing treatment of the embodiment adopts a step-by-step addition mode, and yttrium-based heavy rare earth spheroidizing agent is first added for preliminary spheroidizing, and then MgO@CaO core-shell structure spheroidizing agent and graphite morphology regulating elements are simultaneously added after 50 seconds of reaction for secondary spheroidizing optimization, and the temperature difference of the two-step spheroidizing is controlled within 35°C.
[0104] The yttrium-based spheroidizing agent of the embodiment provides a stable spheroidizing core, the MgO@CaO spheroidizing agent optimizes the graphite sphere morphology through Ca-Mg synergistic effect, and the graphite morphology regulating elements inhibit the formation of flaky graphite.
[0105] The preparation method of the MgO@CaO core-shell structure spheroidizing agent of the embodiment includes the following steps: A1. Core solution preparation: one or more soluble magnesium salts of magnesium sulfate, magnesium chloride or magnesium nitrate are dissolved in deionized water to prepare a magnesium ion solution with a concentration of 2.0 mol / L, sodium dodecyl sulfate is added as a dispersing agent, the addition amount is 0.4% of the weight of the magnesium salt, ammonia water is added as a pH adjuster, the pH value is controlled at 10.5, and the stirring time is 25 minutes.
[0106] A2. Precipitation reaction: ammonia water solution with a concentration of 4 mol / L is added dropwise into the magnesium ion solution at a rate of 2.5 mL / min to completely precipitate the magnesium ions, and the magnesium hydroxide precipitate is generated after reacting at 80°C for 2.5 hours.
[0107] A3. Calcination nucleation: after the magnesium hydroxide precipitate is filtered, washed and dried, it is calcined at 950°C for 3.5 hours to obtain the MgO core.
[0108] A4. Shell coating: the MgO core is dispersed in a calcium chloride solution with a concentration of 2.5 mol / L, and after stirring for 18 minutes, a sodium carbonate solution with a concentration of 1.5 mol / L is added for co-precipitation reaction, and the calcium carbonate shell is generated in situ on the surface of the MgO core after reacting for 3.5 hours.
[0109] A5. Thermal decomposition conversion: the composite particles coated with calcium carbonate are thermally decomposed at 1050°C for 2.8 hours, and the calcium carbonate is decomposed into CaO to form the CaO shell layer.
[0110] A6. Surface modification: cooling at a rate of 8°C / min under an inert atmosphere, and surface modification is performed by introducing water vapor with a volume flow rate of 150 mL / min during the cooling process, and the modification time is 50 minutes, which enhances the interfacial bonding force of the core-shell structure, and the MgO@CaO core-shell structure spheroidizing agent is obtained.
[0111] The large volute part of the present embodiment is prepared by the above method; the chemical composition of the large volute part of the present embodiment is as follows in terms of percentage by weight: C 3.65%, Si 2.3%, Mn 0.6%, P ≤0.05%, S ≤0.02%, Cu 0.65%, Sn ≤0.05%, Y 0.022%, graphite morphology regulating element 0.035%, residual rare earth ≤0.03%, and the balance being Fe and unavoidable impurities.
[0112] The microstructure of the large volute part of the present embodiment includes spheroidal graphite + ferrite + pearlite, the spheroidization rate of graphite is ≥95%, the average diameter of graphite spheres is 25 μm, and there is no flaky graphite.
[0113] The interface between the graphite spheres and the matrix of the present embodiment has a composite transition layer rich in Ca, Mg, C, O and Y elements, and the average thickness is 16.8 μm, which effectively prevents the formation of flaky graphite and improves the interface bonding strength.
[0114] Example 4 seeks the best balance between performance and cost by adopting an optimized balanced parameter design. The carbon content of 3.65% and the silicon content of 2.3% are selected in this example, the ratio of spheroidizing agent is carefully optimized, the yttrium-based heavy rare earth spheroidizing agent is 1.3%, and the processing parameters are moderately controlled to form graphite spheres of 25 μm and interface transition layers of 16.8 μm, which not only ensures excellent mechanical properties but also controls the manufacturing cost. This example embodies the practicality of engineering application, and the process has good stability and reliable performance. The application scenarios are mainly located in professional application fields such as petrochemical pump volute, sewage treatment pump shell, marine seawater pump shell, food-grade centrifugal pump volute, pharmaceutical equipment pump body, etc., which have high requirements on performance but also need to consider economy.
[0115] Comparative Example 1: It is basically the same as Example 1, except that only yttrium-based heavy rare earth spheroidizing agent is added during spheroidizing treatment, no MgO@CaO core-shell structure spheroidizing agent and graphite morphology regulating element is added, the addition amount of yttrium-based heavy rare earth spheroidizing agent is 1.1% by weight of the iron liquid, the treatment temperature is 1470℃, and the spheroidizing treatment time is 5 minutes.
[0116] Comparative Example 2: It is basically the same as Example 1, except that the spheroidizing treatment temperature is 1380℃, and other spheroidizing treatment parameters remain unchanged, the addition amount of yttrium-based heavy rare earth spheroidizing agent is 1.1% by weight of the iron liquid, the addition amount of MgO@CaO core-shell structure spheroidizing agent is 0.5% by weight of the iron liquid, and the addition amount of graphite morphology regulating element is 0.02% by weight of the iron liquid.
[0117] Comparative Example 3: Essentially the same as Example 1, except that a traditional nodulizer is used instead of the yttrium-based heavy rare earth nodulizer, and the traditional nodulizer has a composition of Mg 6%, Si 45%, Ca 2%, and the balance Fe, and the addition amount is 1.1% by weight of the molten iron, and the other processing parameters remain unchanged.
[0118] Comparative Example 4: Essentially the same as Example 1, except that the MgO@CaO core-shell structure nodulizer is a physical mixture of MgO and CaO powders, and does not have a core-shell structure, the particle size of the MgO powder is 100 μm, the particle size of the CaO powder is 35 μm, and the addition amount after physical mixing is 0.5% by weight of the molten iron.
[0119] Comparative Example 5: Essentially the same as Example 1, except that the nodulizing treatment is performed by a one-time simultaneous addition method, and the yttrium-based heavy rare earth nodulizer, the MgO@CaO core-shell structure nodulizer, and the graphite morphology control element are added simultaneously, and no step-by-step nodulizing treatment is performed.
[0120] Comparative Example 6: Essentially the same as Example 1, except that the Y content of the yttrium-based heavy rare earth nodulizer is 25%, the Mg content is 5%, the Si content is 45%, the Ca content is 2%, the Al content is 1.2%, and the balance is Fe, and the addition amount is 1.1% by weight of the molten iron.
[0121] Comparative Example 7: Essentially the same as Example 1, except that the particle size of the MgO core of the MgO@CaO core-shell structure nodulizer is 300 μm, the thickness of the CaO shell layer is 80 μm, the porosity of the MgO core is 30%, and the porosity of the CaO shell layer is 35%.
[0122] Comparative Example 8: Essentially the same as Example 1, except that the nodulizing treatment time is 15 minutes, the other nodulizing treatment parameters remain unchanged, the treatment temperature is 1470°C, and the addition amount of the yttrium-based heavy rare earth nodulizer is 1.1% by weight of the molten iron.
[0123] Comparative Example 9: Essentially the same as Example 1, except that no graphite morphology control element is added, and only the yttrium-based heavy rare earth nodulizer and the MgO@CaO core-shell structure nodulizer are added, and the addition amounts are 1.1% and 0.5% by weight of the molten iron, respectively.
[0124] Comparative Example 10: Essentially the same as Example 1, except that the calcination temperature in the preparation of the MgO@CaO core-shell structure nodulizer is 600°C, and the calcination time is 1 hour, and the resulting MgO core has low crystallinity and there is residual magnesium hydroxide that has not completely decomposed.
[0125] Comparative Example 11: Essentially the same as Example 1, except that the pouring temperature is 1300°C, and the other process parameters remain unchanged, the inoculation treatment temperature is 1435°C, and the nodulizing treatment temperature is 1470°C.
[0126] Comparative Example 12: Essentially the same as Example 1, except that the yttrium-based heavy rare earth nodulizer was added at a dosage of 0.3% by weight of the molten iron, the MgO@CaO core-shell structure nodulizer was added at a dosage of 0.1% by weight of the molten iron, and the graphite morphology regulating element was added at a dosage of 0.001% by weight of the molten iron.
[0127] Comparative Example 13: Essentially the same as Example 1, except that the MgO@CaO core-shell structure nodulizer was not subjected to surface modification treatment during preparation, and was directly naturally cooled under an air atmosphere without interface bonding force enhancement treatment by water vapor.
[0128] Comparative Example 14: Essentially the same as Example 1, except that the C content in the molten iron composition was 4.2%, the Si content was 3.0%, and the Mn content was 1.2%, which exceeded the conventional composition range of ductile cast iron, and other treatment parameters remained unchanged.
[0129] Comparative Example 15: Essentially the same as Example 1, except that the temperature difference of the two-step spheroidization was controlled within 80°C, the yttrium-based heavy rare earth nodulizer was first added at 1470°C for preliminary spheroidization, and after a reaction time of 45 seconds, the MgO@CaO core-shell structure nodulizer and the graphite morphology regulating element were added at 1390°C.
[0130] Performance Test: Mechanical Property - Tensile Strength Test: The tensile strength test was performed on large-scale volute castings to evaluate the basic mechanical property indicators such as tensile strength, yield strength, and elongation of the material. The test principle was based on the stress-strain relationship of the material under unidirectional tensile load, and the mechanical property parameters of the material were determined by gradually increasing the tensile force until the specimen broke. The experimental method used a universal material testing machine, standard tensile specimens (diameter 12.5 mm, gauge length 50 mm) were used, the test speed was controlled within the range of 0.5-5 mm / min, and the test environment temperature was 20±5°C. The standard was GB / T228.1-2010 "Metallic Materials - Tensile Test - Part 1: Method of Test at Room Temperature". Key parameters included a preload not exceeding 10% of the yield load, a strain rate controlled within the range of 10 -5 -10 -1 s -1 , and a clamp centering accuracy of ±0.1 mm. Data processing was performed by recording the load-displacement curve to calculate the tensile strength σb=Pmax / A0, yield strength σs, and elongation δ=(L1-L0) / L0×100%, at least 3 valid specimens were tested for each group, and the results were taken as the arithmetic mean.
[0131] Mechanical property - impact toughness test: impact toughness test is conducted on the large volute casting, aiming to evaluate the toughness and brittle fracture resistance of the material under dynamic load. The test principle is based on pendulum impact test, and the impact work absorbed by the material is calculated by measuring the potential energy difference of the pendulum before and after impacting the sample. The experimental method adopts pendulum impact testing machine, uses standard V-notch impact sample (10mm x 10mm x 55mm, notch depth 2mm), pendulum energy 150J or 300J, impact speed about 5m / s, test temperature 20±2℃. The standard is GB / T 229-2007 "Metallic materials Charpy pendulum impact test method". Key parameters include sample machining accuracy ±0.1mm, notch root radius 0.25±0.025mm, pendulum swing plane perpendicularity to sample axis ≤2°, impact center line deviation ≤0.4mm. Data processing is calculated by impact work AK=(mgh1-mgh2), impact toughness αK=AK / A, where A is the cross-sectional area at the notch, at least 5 samples per test, average value after removing outliers, requiring variation coefficient ≤15%.
[0132] Hardness performance test: Brinell hardness test is conducted on the large volute casting, aiming to evaluate the hardness distribution uniformity of the material and the matrix microstructure characteristics. The test principle is based on the indentation formed by the hard steel ball or hard alloy ball under the action of standard load, and the Brinell hardness value is calculated by measuring the indentation diameter. The experimental method adopts Brinell hardness tester, uses a 10mm diameter hard alloy ball indenter, test force 29420N (3000kgf), holding time 10-15 seconds, test surface roughness Ra≤1.6μm, sample thickness ≥8 times indentation depth. The standard is GB / T 231.1-2009 "Metallic materials Brinell hardness test Part 1: test method". Key parameters include indenter ball surface roughness Ra≤0.05μm, test force application speed 10-70N / s, indentation center distance ≥6 times indentation diameter, distance from sample edge ≥2.5 times indentation diameter. Data processing is calculated by the formula HB=0.102×2F / (πD(D-√(D²-d²))), where F is the test force, D is the indenter diameter, d is the indentation diameter, at least 5 points per sample, taking the arithmetic mean, requiring the deviation of single measurement value from the average value ≤±5%.
[0133] Corrosion resistance test: Neutral salt spray corrosion test is conducted on large volute castings to evaluate the corrosion resistance and surface protection effect of the material in chloride-containing environments. The test principle is based on accelerated corrosion testing, which simulates the salt spray conditions in marine atmospheric environment to evaluate the corrosion rate and corrosion morphology of the material. The experimental method uses a salt spray test chamber, prepares a 5% NaCl solution (pH 6.5-7.2), the test temperature is 35±2℃, the salt spray deposition is 1-2mL / (h·80cm²), the continuous spraying time is 96 hours, the sample size is 150mm×70mm×thickness, the surface roughness Ra≤3.2μm. The standard is GB / T 10125-2012 "Artificial atmosphere corrosion test-salt spray test". Key parameters include salt spray chamber temperature uniformity ±1℃, spray pressure 80-120kPa, sample placement angle 15-30°, sample spacing ≥20mm and not allowed to contact each other. Data processing is done by weighing method to determine the corrosion weight loss, calculating the corrosion rate CR=87600×ΔW / (A×T×ρ), where ΔW is the weight loss, A is the sample area, T is the test time, and ρ is the material density, and digital microscope is used to observe the corrosion morphology to evaluate the corrosion grade, at least 3 samples per group, the results are averaged.
[0134] Fatigue performance test: Rotating bending fatigue test is conducted on large volute castings to evaluate the fatigue strength and fatigue life characteristics of the material under cyclic loading. The test principle is based on the fatigue damage accumulation of the material under repeated stress, which establishes the S-N fatigue curve by applying cyclic loading at different stress levels until the sample breaks. The experimental method uses a rotating bending fatigue testing machine, uses standard fatigue samples (minimum diameter 7.5mm, surface polishing Ra≤0.1μm), test frequency 50±2Hz, room temperature atmospheric environment, stress ratio R=-1, at least 5 stress levels are tested. The standard is GB / T 4337-2015 "Metal material fatigue test-rotating bending method". Key parameters include sample geometric accuracy ±0.01mm, surface without machining defects, load accuracy ±1%, frequency stability ±1Hz, test environment temperature 20±5℃. Data processing is done by recording the fatigue life at different stress levels, using the least squares method to fit the S-N curve lgN=A-BlgS to determine the fatigue limit and fatigue strength, at least 6 samples per stress level, the ascending and descending method is used to determine the fatigue limit, the data dispersion variation coefficient is required to be ≤25%, the fatigue design curve with 95% confidence and 97.5% survival rate is established.
[0135] The properties of the castings of Examples 1-4 and Comparative Examples 1-15 are summarized in Table 1. Comparative Example 1 only uses a single yttrium-based heavy rare earth spheroidal agent, lacking the synergistic effect of the MgO@CaO core-shell structure spheroidal agent and the optimization effect of the graphite morphology regulating element, resulting in irregular graphite sphere morphology, poor spheroidization persistence, weak interface transition layer, and significant decline in mechanical properties and corrosion resistance. The low-temperature spheroidization treatment of Comparative Example 2 makes the spheroidization reaction kinetics insufficient, the Mg vapor pressure low, the spheroidization core difficult to form, the graphite spheroidization rate reduced, and the matrix structure uneven, with simultaneous deterioration of strength and toughness. Comparative Example 3 uses a traditional spheroidal agent lacking the desulfurization and deoxidation purification effect of rare earth elements, with increased residual impurities, weakened grain boundaries, significantly increased corrosion sensitivity, and decreased fatigue performance. The use of physically mixed MgO and CaO powders in Comparative Example 4 cannot achieve the layered release mechanism of the core-shell structure, with low spheroidal agent utilization and unstable spheroidization effect, resulting in uneven graphite sphere size and distribution. The one-time simultaneous addition method of Comparative Example 5 destroys the kinetic advantage of stepwise spheroidization, with adverse reactions between components, reduced spheroidization efficiency, and decreased graphite sphere quality. The excessive Y content in Comparative Example 6 causes the spheroidal agent melting point to rise and the fluidity to deteriorate, while excessive rare earth elements form rare earth compound inclusions, deteriorating the mechanical properties and processing performance of the material. The excessive core-shell structure particle size and high porosity in Comparative Example 7 reduce the reaction activity and dispersion uniformity of the spheroidal agent, leading to insufficient local spheroidization and increased organizational heterogeneity. The excessive spheroidization time of Comparative Example 8 leads to spheroidization recession, excessive oxidation and volatilization of Mg elements, and grain coarsening and overburning of the structure due to high-temperature long-time treatment, severely affecting the comprehensive performance of the material. Comparative Example 9 lacks graphite morphology regulating elements, which cannot effectively inhibit the formation of fragmented graphite, resulting in deteriorated graphite morphology, enhanced stress concentration effect, and decreased impact toughness and fatigue performance. The excessively low calcination temperature in Comparative Example 10 leads to insufficient crystallinity of the MgO core, with residual un-decomposed magnesium hydroxide, reduced spheroidal agent activity, incomplete reaction, and poor spheroidization effect. The extremely low pouring temperature of Comparative Example 11 causes poor iron melt fluidity and difficult filling, as well as increased thermal stress due to excessive temperature gradient, leading to defects in the casting and deteriorated mechanical properties. The spheroidal agent addition amount in Comparative Example 12 is severely insufficient, which cannot provide sufficient spheroidization elements, resulting in low graphite spheroidization rate, a large amount of flaky graphite remaining, and the material exhibiting gray cast iron characteristics with extremely poor strength and toughness. Comparative Example 13 lacks surface modification treatment, with weak core-shell interface bonding force, and the spheroidal agent is prone to separation and failure in the melt, resulting in poor spheroidization stability and suboptimal organizational uniformity. The excessively high alloying degree in Comparative Example 14 exceeds the nodular cast iron composition range, promoting the formation of brittle phases such as cementite, while high carbon and silicon content increases the tendency of casting defects, leading to low material strength, high brittleness, and poor corrosion resistance. The excessive two-step spheroidization temperature difference in Comparative Example 15 destroys the continuity and coordination of the spheroidization reaction, with the second-step addition temperature being too low to affect the spheroidal agent dissolution and diffusion, resulting in unsatisfactory spheroidization effect and ultimately leading to all performance indicators of the material being lower than those of the examples.
[0136] Table 1: Performance summary of castings of Examples 1-4 and Comparative Examples 1-15:
[0137]
[0138] Figure 1 It is clearly shown that the MgO@CaO core-shell structure spheroidizing agent of Example 2 has a complete core-shell morphology, and the MgO core is uniformly coated with the CaO shell layer, which confirms the effectiveness of the preparation process. Figure 2 The XRD phase analysis of shows that the phase structure of MgO and CaO in the spheroidizing agent is clear, and no impurity phase exists, which verifies the purity and crystallinity of the material. Figure 3 The element scanning result of shows that a composite transition layer rich in Ca, Mg, C, O and Y elements is formed on the outside of the graphite ball in the casting prepared by Example 2, and the thickness is uniform and has good continuity, which proves that the synergistic effect of the yttrium-based heavy rare earth spheroidizing agent and the MgO@CaO core-shell structure spheroidizing agent is successfully achieved. Figure 4 The transition layer of Comparative Example 1 is obviously uneven and missing due to the lack of core-shell structure spheroidizing agent, which is in sharp contrast to the examples. Figures 5-7 The performance comparison data of show that the examples are superior to the comparative examples in key performance indicators such as strength, toughness, hardness and fatigue, among which the tensile strength of Example 3 reaches 535 MPa, the impact toughness reaches 14.2 J / cm², and the fatigue limit reaches 240 MPa, which significantly surpasses the traditional spheroidizing technology level, fully verifying the scientificity and advancement of the ternary synergistic spheroidizing technical route of the yttrium-based heavy rare earth spheroidizing agent, the MgO@CaO core-shell structure spheroidizing agent and the graphite morphology control element.
[0139] Finally, it should be noted that: the above examples are only used to illustrate the technical solutions of the present application and not to limit it, although the present application has been described in detail with reference to the above examples, those skilled in the art should understand that any equivalent structural transformation made under the concept of the present application and using the contents of the present application specification and drawings should be covered within the protection scope of the claims of the present application.
Claims
1. A method of producing a large volute casting, characterized by, The method comprises the following steps: S1. preparing iron liquid: scrap steel, pig iron are smelted in proportion, and the components are adjusted to C content of 3.6%-3.8%, Si content of 1.8%-2.5%, and Mn content of 0.3%-0.8%; S2. spheroidizing treatment: yttrium-based heavy rare earth spheroidizing agent, MgO@CaO core-shell structure spheroidizing agent and graphite morphology regulating element are added to the iron liquid, the addition amount of the yttrium-based heavy rare earth spheroidizing agent is 0.8%-1.5% of the weight of the iron liquid, the addition amount of the MgO@CaO core-shell structure spheroidizing agent is 0.3%-0.8% of the weight of the iron liquid, the addition amount of the graphite morphology regulating element is 0.005%-0.05% of the weight of the iron liquid, the treatment temperature is 1460-1480℃, and the spheroidizing treatment time is 3-8 minutes; S3. inoculation treatment: silicon-iron-based stream inoculant is added at a temperature of 1420-1450℃, the addition amount of the inoculant is 0.06%-0.07% of the weight of the iron liquid, and the inoculation time is 1-3 minutes; S4. pouring forming: the treated iron liquid is poured into a spiral case part casting mold, and the pouring temperature is controlled to be 1380-1420℃; The MgO@CaO core-shell structure spheroidizing agent comprises an MgO core and a CaO outer shell layer covering the outer surface of the MgO core; The graphite morphology regulating element is selected from one or more of bismuth, antimony and tellurium; The yttrium-based heavy rare earth spheroidizing agent comprises Y 5%-15%, Mg 3%-8%, Si 40%-50%, Ca 1%-3%, Al 0.5%-2%, and the balance is Fe; The particle size of the MgO core in the MgO@CaO core-shell structure spheroidizing agent is 50-150μm, the thickness of the CaO outer shell layer is 25-45μm, the porosity of the MgO core is 8-15%, and the porosity of the CaO outer shell layer is 12-20%; The spheroidizing treatment adopts a step-by-step adding mode, the yttrium-based heavy rare earth spheroidizing agent is first added for preliminary spheroidizing, after reacting for 30-60 seconds, the MgO@CaO core-shell structure spheroidizing agent and the graphite morphology regulating element are simultaneously added for secondary spheroidizing optimization, and the temperature difference of the two-step spheroidizing is controlled within a range of 20-40℃.
2. A method of producing a large volute casting according to claim 1, wherein The yttrium-based heavy rare earth spheroidizing agent provides a stable spheroidizing core, the MgO@CaO core-shell structure spheroidizing agent optimizes the graphite sphere morphology through Ca-Mg synergistic effect, and the graphite morphology regulating element inhibits the formation of broken blocky graphite.
3. A method of producing a large volute casting according to claim 1, wherein The preparation method of the MgO@CaO core-shell structure spheroidizing agent comprises the following steps: A1. core solution preparation: one or more soluble magnesium salts of magnesium sulfate, magnesium chloride or magnesium nitrate are dissolved in deionized water to prepare a magnesium ion solution with a concentration of 0.8-2.5mol / L, sodium dodecyl sulfate is added as a dispersing agent, the addition amount is 0.1%-0.5% of the weight of the magnesium salt, ammonia water is added as a pH regulator, the pH value is controlled to be 9.0-11.0, and the stirring time is 15-30 minutes; A2. precipitation reaction: 2-5mol / L ammonia water solution is added dropwise into the magnesium ion solution at a rate of 1-3mL / min to make the magnesium ions completely precipitate, and the magnesium hydroxide precipitate is generated by reacting at 60-90℃ for 1-3 hours. A3. Calcination nucleation: after the magnesium hydroxide precipitate is filtered, washed and dried, it is calcined at 800-1000℃ for 2-4 hours to obtain MgO core; A4. Shell coating: the MgO core is dispersed in a calcium chloride solution with a concentration of 1.0-3.0 mol / L, and after stirring for 10-20 minutes, a sodium carbonate solution with a concentration of 0.5-2.0 mol / L is added to carry out a co-precipitation reaction, and a calcium carbonate shell is generated in situ on the surface of the MgO core after a reaction time of 2-4 hours; A5. Thermal decomposition conversion: the composite particles coated with calcium carbonate are thermally decomposed at 900-1100℃ for 2-3 hours, and the calcium carbonate is decomposed into CaO to form a CaO shell layer; A6. Surface modification: under an inert atmosphere, the temperature is cooled at a rate of 5-10℃ / min, and water vapor with a volume flow rate of 50-200 mL / min is introduced during the cooling process to carry out surface modification, and the modification time is 30-60 minutes, which enhances the interfacial bonding force of the core-shell structure, and a MgO@CaO core-shell structure spheroidizing agent is obtained.
4. A large volute casting characterized by, Prepared by the preparation method of any one of claims 1-3; The chemical composition of the large volute casting is as follows in terms of weight percentage: C 3.6%-3.8%, Si 1.8%-2.5%, Mn 0.3%-0.8%, P ≤0.05%, S ≤0.02%, Cu 0.3%-0.8%, Sn ≤0.05%, Y 0.005%-0.03%, graphite morphology regulating element 0.005%-0.05%, residual rare earth ≤0.03%, and the balance being Fe and unavoidable impurities.
5. A large volute casting as claimed in claim 4, wherein The microstructure of the large volute casting includes spheroidal graphite, ferrite and pearlite, the graphite spheroidization rate is ≥95%, the average diameter of the graphite ball is 15-30 μm, and there is no flaky graphite.
6. A large volute casting as claimed in claim 4, wherein There is a composite transition layer rich in Ca, Mg, C, O and Y elements at the interface between the graphite ball and the matrix, and the average thickness is 12-18.5 μm, which effectively prevents the formation of flaky graphite and improves the interfacial bonding strength.
7. The use of a large volute casting according to claim 4, characterized in that The large volute casting has an application in a water pump, a fan or a compressor, the tensile strength of the large volute casting is ≥500 MPa, the elongation is ≥7%, the Brinell hardness is 170-220 HB, and the large volute casting has excellent corrosion resistance and mechanical properties, and is suitable for thick section castings with a wall thickness of 20-100 mm.
Citation Information
Patent Citations
Low-temperature nodular cast iron, preparation method and QT400-18L volute casting
CN120138494A
Casting thick large-section pearlite nodular cast iron and casting method thereof
CN102965567A
Molten iron inoculation process for large-section low-temperature ferritic nodular cast iron
CN106756442A